Antígonas Tribunal de Mujeres:: archives and poetic repertoires of the memory of a nation in war and transformation - NOGUERA DURAN, ANA MARIA (Revista Brasileira de Estudos da Presença, 2024)
Antígonas Tribunal de Mujeres: archives and poetic repertoires of the memory of a nation in war and transformation – This article analyzes from a perspective of research in political performance, the process of creation and production of the play Antígonas Tribunal de Mujeres, composed of victims and survivors of the war in Colombia, who share in common have suffered state crimes. Taking this case as the object of study, it investigates the methodological routes of creation that these women have created to transform their own stories of pain and resistance into archives and poetic repertoires. Which we postulate as forms of production and transmission of incorporated knowledge, about the memory of a nation marked by violence.